2016
DOI: 10.1523/jneurosci.4280-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Switch in Spike Timing-Dependent Plasticity and Cannabinoid-Dependent Reorganization of the Thalamocortical Projection in the Barrel Cortex

Abstract: The formation and refinement of thalamocortical axons (TCAs) is an activity-dependent process (Katz and Shatz, 1996), but its mechanism and nature of activity are elusive. We studied the role of spike timing-dependent plasticity ( Here we show that TCA-cortical plate synapses exhibit robust t-LTP in neonates, whose magnitude decreased gradually after P4-P5. After L2/3 is differentiated, TCA-L2/3 gradually switched to STDP with only depression (t-LTD) after P7-P8, whereas TCA-L4 lost STDP. t-LTP was dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 56 publications
3
33
0
Order By: Relevance
“…This developmental change in the STDP rule may contribute to reorganization of thalamocortical and intracortical circuits (Itami & Kimura, ). Interestingly, the switch of STDP is associated with the developmental appearance of thalamus‐L2/3 synapses expressing cannabinoid type 1 receptor (Itami et al., ). It has been also suggested that GABAergic interneurons may control STDP rules and that GABA acts as switch of Hebbian synaptic plasticity (Paille et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This developmental change in the STDP rule may contribute to reorganization of thalamocortical and intracortical circuits (Itami & Kimura, ). Interestingly, the switch of STDP is associated with the developmental appearance of thalamus‐L2/3 synapses expressing cannabinoid type 1 receptor (Itami et al., ). It has been also suggested that GABAergic interneurons may control STDP rules and that GABA acts as switch of Hebbian synaptic plasticity (Paille et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It remains unknown how LTP of the postsynapse is conveyed to the presynaptic terminal to elicit structural changes [36]. Retrograde messengers like nitric oxide, arachidonic acid, and eCBs may act as one potential mechanism of pre-post coordination of structural plasticity [37, 38]. …”
Section: Structural Changesmentioning
confidence: 99%
“…Illustration adapted from Itami et al . () with modifications. [Colour figure can be viewed at wileyonlinelibrary.com].…”
Section: Resultsmentioning
confidence: 80%
“…This pairing stimulation consistently resulted in t‐LTD (Fig. B), which was also consistent with our previous study (Itami et al ., ). As a whole, EPSPs decreased to 75.1 ± 7.4% of baseline as summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation